Virtually Treatable: Temporalities and Encodings of Traumatic Experiences - Michael Friedman; Kathrin Friedrich (Angles)
With Freud’s groundbreaking essay “Beyond the Pleasure Principle,” the temporality and treatability of trauma, its triggers and its symptoms, obtained a special status. Not only did Freud imply that trauma cannot be represented, he also eventually stated that analysis itself can never reach a definitive conclusion — analysis is an endless process, literally interminable in Freud’s words. Moreover, the triggering of a trauma was arbitrary, and in no way apparent. This was due to the fact that according to Freud the trauma was triggered retroactively, regardless of when the trigger starts or stops being traumatic. On the background of this unique Freudian temporal retroactivity, this article constructs how new digital and virtual technologies of the 21st century prompt a new understanding of the temporality of the trauma. While the nature of Freudian trauma is temporally unpredictable, we claim that two current virtual reality (VR) technologies used by the US military promise exactly the opposite. The first, called Bravemind, offers soldiers a way to control their experienced traumas by codifying them in virtual scenarios with visual and haptic interfaces under the paradigm of virtual treatment; the second, STRIVE, prepares solders who have not yet been deployed on the battlefield for possible future traumas. In this sense, we claim that STRIVE offers a negative mirror-reflection of the Freudian conception of trauma, and with it, a new conception of trauma itself. For Freud trauma was triggered retroactively, its ontological status was unfixed and trauma itself — its content — unrepresentable. By contrast, with STRIVE the content of trauma is known in advance, and enacted even if it is uncertain whether the anticipated traumatic event will occur.